Exploring the Role of Recreational Sports in Improving the Quality of Life in South Jakarta: A Multigenerational Study - Dameria, Franciska Dina; Setiakarnawijaya, Yasep; Ilham; Hadi; Ishak, Asmadi Bin (JSES : Journal of Sport and Exercise Science, 2025)
Purpose: This study aims to examine the role of recreational sports in improving the quality of life among urban residents in South Jakarta through a multigenerational perspective. It seeks to understand how participation in non-competitive physical activities contributes to physical health, psychological well-being, social connection, and spiritual fulfillment across different age groups. Materials and Methods: The research employed a qualitative exploratory–descriptive approach to capture participants’ lived experiences and personal meanings of recreational sport. Twenty respondents representing four generations: Generation Z, Millennials, Generation X, and Baby Boomers, were purposively selected. Data were gathered through semi-structured interviews and short field observations focusing on activity type, motivation, perceived benefits, intergenerational interactions, and participation barriers. Thematic analysis was used to identify recurring patterns, similarities, and differences among generations. Data validity was strengthened through triangulation, participant verification, and reflective analysis. Result: The study revealed that recreational activities such as walking, gymnastics, yoga, and futsal significantly enhance physical fitness, emotional balance, and social relationships. Participants viewed these activities as opportunities for relaxation, stress relief, and self-expression. Intergenerational engagement fostered empathy and social cohesion, while some respondents associated recreational sport with spiritual awareness and gratitude. However, constraints such as limited open spaces, uneven access to facilities, and safety concerns remained significant challenges. Conclusion: Recreational sport serves as a multidimensional avenue for promoting health, emotional resilience, and intergenerational harmony. Integrating inclusive and accessible recreational programs into urban planning is essential for building healthier, more connected, and sustainable communities.